Biopunk Dystopias Genetic Engineering, Society and Science Fiction - Schmeink, Lars (Liverpool Science Fiction Texts and Studies, 2017)
'Biopunk Dystopias' contends that we find ourselves at a historical nexus, defined by the rise of biology as the driving force of scientific progress, a strongly grown mainstream attention given to genetic engineering in the wake of the Human Genome Project (1990-2003), the changing sociological view of a liquid modern society, and shifting discourses on the posthuman, including a critical posthumanism that decenters the privileged subject of humanism. The book argues that this historical nexus produces a specific cultural formation in the form of "biopunk", a subgenre evolved from the cyberpunk of the 1980s. Biopunk makes use of current posthumanist conceptions in order to criticize contemporary reality as already dystopian, warning that a future will only get worse, and that society needs to reverse its path, or else destroy all life on this planet.